2008
DOI: 10.1614/wt-07-111.1
|View full text |Cite
|
Sign up to set email alerts
|

Carrier Volume Affects Wheat Response to Simulated Glyphosate Drift

Abstract: The influence of carrier volume was evaluated in field experiments for glyphosate applied to wheat at rates representing 12.5 and 6.3% of the usage rate of 1,120 g ai/ha (140 and 70 g/ha, respectively). Wheat at first node and at heading was exposed to glyphosate applied in a constant carrier volume of 234 L/ha, where herbicide concentration declined with reduction in dosage, and in proportional carrier volumes of 30 L/ha for the 12.5% rate and 15 L/ha for the 6.3% rate, where herbicide concentration remained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 27 publications
(36 reference statements)
2
24
1
Order By: Relevance
“…In 2010, grain sorghum yield was reduced 73% when applied in the constant carrier volume of 224 L ha À1 compared to a yield reduction of 55% when applied in the proportional carrier volume averaged across 56, 28, and 14 L ha À1 . These data are in contrast to those previously reported for 2,4-D on cotton (Gossypium hirsutum L.) and for glyphosate on sweet corn (Zea mays L.) (Banks and Schroeder 2002) and for glyphosate on corn (Ellis et al 2002) and for glyphosate on wheat (Triticum aestivum L.) (Roider et al 2008). A possible explanation for this is the number of droplets deposited on the grain sorghum leaves.…”
Section: Resultscontrasting
confidence: 97%
See 2 more Smart Citations
“…In 2010, grain sorghum yield was reduced 73% when applied in the constant carrier volume of 224 L ha À1 compared to a yield reduction of 55% when applied in the proportional carrier volume averaged across 56, 28, and 14 L ha À1 . These data are in contrast to those previously reported for 2,4-D on cotton (Gossypium hirsutum L.) and for glyphosate on sweet corn (Zea mays L.) (Banks and Schroeder 2002) and for glyphosate on corn (Ellis et al 2002) and for glyphosate on wheat (Triticum aestivum L.) (Roider et al 2008). A possible explanation for this is the number of droplets deposited on the grain sorghum leaves.…”
Section: Resultscontrasting
confidence: 97%
“…These results showing greater yield reduction in 2012 are likely attributable to reduced rainfall during the growing season (Table 1), perhaps due to decreased herbicide metabolism as the plants adjusted to drier conditions. The increased yield reduction from the proportional carrier volumes agree with results reported for glyphosate (Banks and Schroeder 2002;Ellis et al 2002;Roider et al 2008) but disagrees with 2010 results. A possible explanation could be increased epicuticular wax loads on grain sorghum plants in 2012.…”
Section: Resultssupporting
confidence: 47%
See 1 more Smart Citation
“…Herbicide effects from volatilization exposure would be more highly overestimated in these simulated drift experiments since spray exposure is chronic as opposed to an acute and transient vapor exposure (due to air mixing and lack of particle deposition). On the other hand, some herbicides can show an increased response when applied at lower spray volumes and therefore higher concentrations (Banks and Schroeder 2002;Roider et al 2008). However, these studies can be instructive for correlating visual symptoms with other plant parameters such as growth and grain yield.…”
Section: Nontarget Plant Sensitivitymentioning
confidence: 99%
“…It is likely that the practice of simulating spray drift by dilution rather than by using proportionally decreasing spray volumes has led to a significant underestimation of the negative effects of spray drift on plants in many cases, potentially by as much as a factor of 4, although this is difficult to ascertain. Roider et al found a wheat yield decrease of 11% when applying glyphosate at a rate of 70 g/ha and a spray volume of 234 L/ha but a decrease of 42% when glyphosate was applied in a proportional carrier volume of only 15 L/ha. Similarly, Ellis et al , using the same application rates and spray volumes, found a 4 times higher yield reduction of corn; and Banks and Schroeder obtained a >4 times lower no‐observed‐effect level value when using proportional carrier volumes compared with a constant one.…”
Section: Resultsmentioning
confidence: 99%